2006
DOI: 10.2307/25063073
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Production and Exchange in Late/Terminal Formative Period Oaxaca

Abstract: Patterns of Late/Terminal Formative period (ca. 500 B.C.–A.D. 300) ceramic exchange in Oaxaca are examined through instrumental neutron activation analysis (INAA). Samples of 453 Late/Terminal Formative period sherds were submitted to the Missouri University Research Reactor for INAA to determine elemental composition. The sherds came from 20 excavated sites and two surveys in the following regions: the Valley of Oaxaca, Mixteca Alta, Mixteca Baja, lower Río Verde Valley, and Cuicatlán Cañada. Selected for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…The presence of broadly similar G.12 bowls over multiple regions probably reflects the exchange of stylistic information among producers and users in numerous locales, through modes of interaction that were relatively informal and not greatly distorted by political interference. To draw a contrast, it is likely that the G.12 distribution during the Late Monte Alban I and Monte Alban II phases was less affected by political affI1ia-tion between individual communities and Monte Alban than was the distribution of contemporaneous types of the cream or crema ware (e.g., Co2, C.6, C.7, C.ll, C.12, C.13, Co20); all crema wares were evidently produced with clay from deposits in the near vicinity of Monte Alban itself Feinman 1982: 188-191;Flannery and Marcus 1994: 22 ;Joyce et al 2006). Indeed, recent excavations of Monte Alban II phase kilns near the Main Plaza of Monte Alban yielded a predominance of these crema wares (MartInez Lopez and Markens 2004: 91;Markens and MartInez LOpez 2004).…”
Section: The G12 Grayware Bowl: Stylistic Variation Microtypology mentioning
confidence: 99%
“…The presence of broadly similar G.12 bowls over multiple regions probably reflects the exchange of stylistic information among producers and users in numerous locales, through modes of interaction that were relatively informal and not greatly distorted by political interference. To draw a contrast, it is likely that the G.12 distribution during the Late Monte Alban I and Monte Alban II phases was less affected by political affI1ia-tion between individual communities and Monte Alban than was the distribution of contemporaneous types of the cream or crema ware (e.g., Co2, C.6, C.7, C.ll, C.12, C.13, Co20); all crema wares were evidently produced with clay from deposits in the near vicinity of Monte Alban itself Feinman 1982: 188-191;Flannery and Marcus 1994: 22 ;Joyce et al 2006). Indeed, recent excavations of Monte Alban II phase kilns near the Main Plaza of Monte Alban yielded a predominance of these crema wares (MartInez Lopez and Markens 2004: 91;Markens and MartInez LOpez 2004).…”
Section: The G12 Grayware Bowl: Stylistic Variation Microtypology mentioning
confidence: 99%
“…Subsequently, INAA was conducted on buff (crema) sherds from Monte Albán. Results showed strong correlations with modern Atzompa pottery (Joyce et al 2006).…”
Section: Acknowledgmentsmentioning
confidence: 90%
“…were identified archaeologically during the Valley of Oaxaca Settlement Pattern project (Kowalewski et al 1989:94). They are located near sources of clays used by modern Atzompa potters (figure 2), and sourcing studies have shown that clays from the Atzompa source zone were used in the production of Formative to Post Classic buff wares at Monte Albán (Shepard 1967;Thieme 2001;Joyce et al 2006). 2 Classic Period (400-700 C.E.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another indication of status differences was the discovery of hundreds of sherds from vessels imported into the lower Río Verde Valley from the Oaxaca Valley, the Mixteca Alta, and an as yet unidentified region (as determined by INAA, ICP, and petrographic analyses; see Banker and Joyce 1991;Joyce 1991c;Joyce et al 2006;Workinger 2002, 345-369). These sherds were recovered at Cerro de la Cruz, Río Viejo, and San Francisco de Arriba in contexts with other evidence of public ritual activity or high status, indicating that they were imported as social valuables (Joyce 1991a, 517-519;Joyce et al 2006;Workinger 2002, 389-390;Chapter 7). The establishment of long-distance exchange relations and the acquisition of exotic goods through these networks were means through which people set themselves apart from others (see below).…”
Section: Early Settlement and Social Complexitymentioning
confidence: 99%